Use of social media sites as a source of information about dental treatment options, clinics, and practitioner - Bhattarai, Rosina; Luitel, Priyanka; Bhandari, Ritu (Journal of Chitwan Medical College, 2025)
Introduction: Internet and social media today have become an integral part of our lives, a source of information in healthcare, including dentistry. This study was carried out to find out the use of social media sites for information on dental treatment options, dental clinics and dental practitioners. Method: Cross-sectional study was conducted among 362 participants from Apr to Jun 2024. Information was collected from people residing in Bharatpur, Chitwan, Nepal, who were approached during the community programs, using pre-designed proforma. Face-to-face interview method was employed to collect information after obtaining consent from the participants and ethical clearance from the IRC. Descriptive statistics were presented where for categorical variables frequencies and percentages were given and for continuous variables mean and standard deviation were given. Chi square test was applied to find out the association of the social media use for dentistry with gender. Data entry was done in Microsoft Excel and data analysis in IBM SPSS version 20. Result: Total of 362 participants was included in the study with mean age of 27.89±8.16 and age range of 18 to 55 years. 351(97%) of the study participants use Facebook, followed by 283(78.2%) Instagram users. Among the study participants, 42(36.8%) males and 76(30.6%) females follow dentist/dental clinic on social media. Among the males, 68(59.6%) and females 121(48.8%) would go to a dentist based on before and after pictures posted in social media. Conclusion: Social media is being used widely and affect the choice in dental treatment and selection of dental clinic.